Thermal evolution of CaO-doped HfO2 films and powders - Barolin, S. A. (2009)
Solid solutions of ZrO2 and HfO2 are potential electrolyte materials for intermediate-temperature SOFC because both are oxygen-ion conductors. The main challenge for these compounds is to reduce the relatively high value of the activation energies vacancies diffusion, which is influenced by several factors. In this work the thermal evolution of CaO-HfO2 materials have been investigated. (CaO)y-Hf(1-y)O(2-y) (y 0.06, 0.14 y 0.2) coatings and powders were synthesized by chemical solution deposition (CSD). Films were deposited onto alumina substrates by Dip Coating technique, the burning of organic waste was carried out at 500 °C under normal atmosphere and then the films were thermally treated at intervals of temperature rising to a maximum temperature of 1250 °C. By means Glazing Incidence X-ray Diffraction (ρ-2θ configuration) the phases were studied in the annealed films. On the other hand, the thermal evolution and crystallization process of powders were analyzed in-situ by HT-XRD. The phenomena crystallization occurred in films and powders were analyzed. The activation energies of diffusion of oxygen vacancies of HfO2-14 mole% CaO and HfO2-20 mole% CaO films were measured from the thermal evolution of the relaxation constant measured by Perturbed Angular Correlation Technique.